Dynasties and destiny: On the roles of altruism and impatience in the evolution of consumption and bequests - Oded Stark; Ita Falk (University of Bonn, Center for Development Research (ZEF), 2001)
We study the joint role of altruism and impatience, and the impact of evolution in the formation of long-term time preferences and in the determination of optimal consumption and optimal bequests. We show how the consumption paths of dynasties relate to altruism and to impatience, and we reason that long-lived dynasties will be characterized by a higher degree of altruism and a lower degree of impatience than short-lived dynasties.
Keywords: 330; Institutional and Behavioral Economics; Soziale Werte; Altruismus; Intergenerationale Übertragung; Konsum; Erbe; Theorie